2017
DOI: 10.1007/s00259-017-3831-0
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]Pentixafor-PET/MRI for the detection of Chemokine receptor 4 expression in atherosclerotic plaques

Abstract: PurposeThe expression of chemokine receptor type 4 (CXCR4) was found co-localized with macrophages on the atherosclerotic vessel wall and participated in the initial emigration of leukocytes. Gallium-68 [68Ga]Pentixafor has recently been introduced for the imaging of atherosclerosis by targeting CXCR4. We sought to evaluate human atherosclerotic lesions using [68Ga]Pentixafor PET/MRI.MethodsThirty-eight oncology patients underwent [68Ga]Pentixafor PET/MR imaging at baseline. Maximum standardized uptake values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Obviously, not all lesions observed on PET in vivo can be verified by histology (which applies to all clinical atherosclerosis studies). However, there are recent clinical studies evaluating the usefulness of pentixafor for CXCR4 imaging in plaque [ 14 , 38 ], and also studies which have demonstrated that the arterial wall uptake can be blocked, is specific, reproducible, and correlates with the presence of CXCR4 + cells [ 16 , 38 ]. In addition, the ex vivo data presented in this work confirm the presence of CXCR4 + cells in the coronary wall, and demonstrate an increasing number of these cells with advancing pathology of lesions, in line with the observed in vivo PET data.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, not all lesions observed on PET in vivo can be verified by histology (which applies to all clinical atherosclerosis studies). However, there are recent clinical studies evaluating the usefulness of pentixafor for CXCR4 imaging in plaque [ 14 , 38 ], and also studies which have demonstrated that the arterial wall uptake can be blocked, is specific, reproducible, and correlates with the presence of CXCR4 + cells [ 16 , 38 ]. In addition, the ex vivo data presented in this work confirm the presence of CXCR4 + cells in the coronary wall, and demonstrate an increasing number of these cells with advancing pathology of lesions, in line with the observed in vivo PET data.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger human study of 38 patients, 611 foci of Ga-68 Pentixafor uptakes were seen in the vessels (Li et al 2017). The intensity of uptake correlated positively with the presence of CVD risk factors (male gender, diabetes, hypertension, hypercholesterolemia).…”
Section: Chemokine Receptor-based Imagingmentioning
confidence: 93%
“…To further investigate the hypothesis that CXCR4 signal reports the level of endothelial injury in atherosclerosis, we compared 64 Cu-DOTA-vMIP-II to 64 Cu-DOTA-FC131, a CXCR4 specific tracer. Although PET signals arising from CXCR4-specific tracer is already reported in atherosclerosis (41)(42)(43)(44), the plaque characteristics, or biological parameters of plaque activity, that may or may not correlate with its PET signal are still not fully understood. Similar to studies with the vMIP-II tracer ( Fig.…”
Section: Cxcr4 Specific Pet Tracer Also Accumulates In Plaque Ecs Andmentioning
confidence: 99%